2015
DOI: 10.5935/abc.20150134
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Resistance Promotes Mild Contractile Dysfunction Associated with Intracellular Ca2+Handling

Abstract: BackgroundDiet-induced obesity is frequently used to demonstrate cardiac dysfunction. However, some rats, like humans, are susceptible to developing an obesity phenotype, whereas others are resistant to that.ObjectiveTo evaluate the association between obesity resistance and cardiac function, and the impact of obesity resistance on calcium handling.MethodsThirty-day-old male Wistar rats were distributed into two groups, each with 54 animals: control (C; standard diet) and obese (four palatable high-fat diets) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, some individuals remain resistant to becoming obese, a condition also observed in some animals' fed with high-fat diets, which are defined as obesity-resistant animals. [8][9][10]24,25 Within this context, some authors have reported that around 40% of the animals fed with a high-fat diet are classified as ROb. [8][9][10]23 Some possible pathways to explain the obesity resistance include: increased expression of some thermogenic enzymes and decreased expression of lipogenic enzymes in adipose tissues of ROb rats, as well as the suppression of lipogenesis and the acceleration of fatty-acid oxidation in visceral fat.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some individuals remain resistant to becoming obese, a condition also observed in some animals' fed with high-fat diets, which are defined as obesity-resistant animals. [8][9][10]24,25 Within this context, some authors have reported that around 40% of the animals fed with a high-fat diet are classified as ROb. [8][9][10]23 Some possible pathways to explain the obesity resistance include: increased expression of some thermogenic enzymes and decreased expression of lipogenic enzymes in adipose tissues of ROb rats, as well as the suppression of lipogenesis and the acceleration of fatty-acid oxidation in visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, no studies have evaluated the contribution of collagen expression to cardiac remodeling in obesity-resistant animal models, and the few studies that evaluated the cardiac changes in this condition found divergent results. Sá et al 9 found isolated papillary muscle contraction impairment, while Carroll et al 10 found cardiac no abnormalities in obesity-resistant animals fed with a high-fat diet.…”
Section: Metabolic and Hormonal Evaluationmentioning
confidence: 99%
See 3 more Smart Citations